Microsoft SharePoint 2007 technologies planning, design and implementation - Laahs, Kevin; McKenna, Emer.; Vanamo, Veli-Matti. (Oxford : Digital, 2008)
Microsoft SharePoint 2007 Technologies: Planning, Design and Implementation provides an in-depth examination of the tasks involved in planning, designing and deploying SharePoint in your enterprise. SharePoint 2007 significantly extends the breadth of capabilities for end users, administrators, developers, and designers. The cutting-edge technology encompasses some major new functional areas such as Business Intelligence, Information LifeCycle Management, and Enterprise Content Managementall can be leveraged to satisfy many different business scenarios. SharePoint 2007 Technologies will provide readers with practical knowledge and techniques about integration of other 2007 products such as Office and Exchange Server, and readers will walk away with the ability to easily expose and leverage back-end business data and understand how it all joins together. Readers will further gain a solid appreciation of the architecture, administration, end user features, development, and integration opportunities offered by SharePoint 2007. The expertise of the author team in helping many large corporations deploy Microsoft technologies within their enterprises makes this book an invaluable tool to businesses of any size. * Complete guide to getting the most out of your SharePoint 2007 deployments * Critical techniques for system architects to design and deploy SharePoint 2007 Technologies * Features most important issues for day to day efficient management and usage * How to customize and extend your SharePoint environment for your own needs.
Part I: Product Overview and Major Components -- Ch 1Microsoft Office SharePoint Server 2007 Architecture -- Ch 2 Upgrading and Migrating to SharePoint Server 2007 -- Ch 3 Planning a SharePoint Server 2007 Deployment -- Ch 4 Planning Extranet Deployments -- Ch 5 Deploying SharePoint Server 2007 -- Ch 6 Disaster Recovery -- Ch 7 SharePoint Server 2007 Operations -- Ch 8 Supporting SharePoint Server 2007 -- Part II: Planning, Deployment and Operations -- Chapter 9 SharePoint Concepts and Architecture -- Chapter 10 Building and Deploying Web Parts -- Chapter 11 Branding your SharePoint 2007 Sites -- Chapter 12 Site Definitions and Site Templates -- Chapter 13 Features -- Chapter 14 SharePoint Programmability -- Chapter 15 Events -- Chapter 16 Workflow -- Chapter 17 InfoPath Forms Services -- Chapter 18 Supporting SharePoint Server 2007 -- Part III: Customizing and Extending SharePoint-ERM -- Chapter 19 SharePoint Concepts and Architectures -- Chapter 20 Building and Deploying Web Parts -- Chapter 21 Branding your SharePoint 2007 Sites -- Chapter 22 Site Definitions and Site Templates -- Chapter 23 Features -- Chapter 24 SharePoint Programmability -- Chapter 25 Events -- Chapter 26 Workflow -- Chapter 27 InfoPath Forms Services.
Includes index.
Keywords: Microsoft SharePoint (Electronic resource); Web servers; Intranets (Computer networks); Electronic books